A Comparative Study On the Academic Performance of Day Scholar and Hostel Medical Undergraduate Students: Life Sciences -Anatomy - Priyanka, G.; Kumaresan, M.; Achuthan, Sangeetha; K, Chaturitha.; Raghunath, Gunapriya (International Journal of Life Science and Pharma Research, 2023)
Examinations are the greater source of anxiety in medical education, and they can be greatly affected by the residential status of medical students. The study compares the academic performance between the day scholar students and the hostelers pursuing the first year of MBBS. This study was conducted at Saveetha Medical College, Chennai, India. Assessment of the marks obtained by both groups of students was done. Two exams, one theory and one practical exam, including viva voce, were taken for analysis. All 149 students attended both exams. Students in both categories were divided into 4 groups according to the marks obtained. Students who obtained < 50% marks were categorized as Group A, 50 to 69 % as Group B, 70% to 89% as Group C, and> 90% as Group D. In this study, 149 students participated. Among these, 82 students (55.03%) were day scholars, and 67 (44.96%) were hostelers. In the theory exam, 59.8% of day scholars belonged to Group B compared to 55.2% of hostelers. Only 6.09% of day scholar students were in group A as opposed to 19.4% of Hostelers in the same group. In Practical exams, amongst day scholars, 52.4% were in group B compared to 46.2% of hostelers in the same group. Only 4.9% of day scholars were in Group A as opposed to 19.4% of hostelers in the same group. There was a significant difference academically between the two groups of students involved in this study. The day scholars performed better than Hostelers in academics.